(3bdGOI GdfMQ aj hajGJ CYjGf GdOgQs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s
(3ChdgG (B:s
(3jHJOF HChd SfI (B321(3g` s
(3fSNI eUhQI Yf fSNI Hfi LGeY HGdBSJGfI Qbe (B88s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B240 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B206 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B167) s
Keywords: (3GdJGQjNs